The Application of Risk Management in Business Decision Making in Retail Companies: A Case Study at PT Indomarco Prismatama (Indomaret) Makassar Branch - Nasir, Nasir (RADINKA JAYA UTAMA PUBLISHER, 2025)
In a competitive and dynamic retail business environment, the implementation of risk management is an important aspect in supporting effective decision-making. This research aims to describe and analyze how risk management is applied in the business decision-making process at PT Indomarco Prismatama (Indomaret) Makassar Branch. The method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that the company has implemented risk management systematically through the identification of operational risks, the use of stock monitoring technology, and the preparation of alternative scenarios in the face of uncertainty. The implementation of risk management has been proven to speed up the decision-making process, improve operational efficiency, and minimize potential losses. However, there were also several obstacles such as the lack of risk training for new staff and differences in perceptions of the urgency of risk among work units. Based on these findings, it is recommended that companies improve risk management training regularly, strengthen internal coordination, and optimize data-driven digital systems to support more responsive and adaptive decision-making.